A straightforward approach to carborane-substituted BODIPY derivatives via nucleophilic aromatic substitution: Synthesis and photodynamic properties. (November 2022) - Zaitsev, Andrei V.; Kononova, Elena G.; Markova, Alina A.; Shibaeva, Anna V.; Kostyukov, Alexey A.; Egorov, Anton E.; Kuzmin, Vladimir A.; Shtil, Alexander A.; Ol'shevskaya, Valentina A.
Abstract: Neutral and water soluble anionic carborane derivatives of 4, 4-difluoro-4-bora- 3a, 4a -diaza- s -indacene (BODIPY) were efficiently synthesized via nucleophilic aromatic substitution of p -fluorine atom in meso -8-pentafluorophenyl-substituted BODIPYs with carborane S-nucleophiles. Using this synthetic approach a series of thiocarboranyl-BODIPYs was generated in good yields under mild reaction conditions such as room temperature and a short reaction time. Individual carborane-BODIPY conjugates formed stable complexes with serum albumin and generated singlet oxygen. In cell based experiments compounds 6 (8-[4-(( m -carboran-9-yl)thio)-2, 3, 5, 6-tetrafluorophenyl]-4, 4-difluoro-4-bora- 3a, 4a -diaza- s -indacene) and 11 (8-[4-((1-carba- closo -dodecaboran-1-yl)thio)-2, 3, 5, 6-tetrafluorophenyl]-1, 3, 5, 7-tetramethyl-4, 4-difluoro-4-bora- 3a, 4a -diaza- s -indacene caesium) were negligibly cytotoxic in the dark whereas the plasma membrane photodamage and cell death were registered rapidly after illumination. Thus, the new chemotype of boronated BODIPYs emerges as a biocompatible and efficient tool for binary therapeutic modalities. Graphical abstract: Image 1 Highlights: Neutral and water-soluble anionic carborane BODIPY derivatives were synthesized. Compounds demonstrated high fluorescence quantum yields and formed complexes with albumin. Photoactivation of tumor cells loaded with selected compounds triggered rapid necrosis.